Parametric study on bored pile retaining wall with rear relieving slab - Wong, Ken Wei. (2008)
The lateral wall displacements for free cantilever bored pile retaining wall can be excessive. Lateral supports which help to minimise wall displacements are not always possible or economical. By introducing a relieving slab at the rear of the cantilever bored pile retaining wall, the magnitude of deflection and bending moment in the bored pile wall are reduced, thereby optimising the design of the retaining system and reducing the construction period. Site topography which require the bored pile retaining wall to be extended upwards and subsequently backfilled can be suitable for the application of the relieving slab behind the wall.